۱۹۷۰ء کے بعد کا افسانہ شمس الرحمٰن فاروقی کی نظر میں - Dr. Rabia Bibi; Dr. Altaf Yousafzai; Dr. Abid ALi (Khayaban - خیابان, 2023)
Shab Khoon was a trendy magazine.This magazine played an important role in promoting thetrend of modernity.Fiction written around the 1960s trends to be more Extreme.Fiction writersmade new experiments in fiction.The new fiction has disturbed People a lot,sometimes there is no characters,sometimes prose poems are being writtenIn the name of prose,and sometimes the use of symbols has made the fiction difficult.ThePurpose of modernization was to attract people to new possibilities.Gradually,the extremism of fiction writers also decreased.In these modern fictions there is an assimilation in the trend Of modernity.Looking at the technical and intellectual changes in fiction written after 1970s Literary critics said that the trend of modernism has ended ,now the era of post-modernism has begun.During this period,Shab khun,s fiction section increased.Shamsur-Rehman Farooqi says that a special type of fiction that was being written around 1960,if the same kind of fiction Is not being written today,I have never called these things the essence of modernity .I have always said that four or five basic concept.Those who follow them are modern.It does not matter whether He is writing abstract fiction,difficult fiction or simple.It can also be that a fiction is difficult but not modern and a fiction is easy and modern.Modernity as a guiding principle in literary civilization is established and stable not only here but in Urdu but also in large part of the modern world.There is none of the basic principles of modernity that have been erased from the pages of literature anywhere in the world today.Modernism is the name of a way of thinking and a concept.Shams-ur-Rehman Farooqi used to say that if the modern generation defines itself with modernity,then they can be separated.When the trend of modernity has run its course,another theory of literature will take its place.He used to say that I do not consider literary principles and ideas to be absolute universal and timeless. Modernism is not a religion or devine philosophy that is disbelief.From 1966 to 2005 ,his magazine was published continuously.Through this magazine,many fictions reached the readers.Many fictions reached the readers.Many new fiction writers were introduced to the literary world.